Effective Training Methods for Improving the Performance of Table Tennis Athletes: A Systematic Review - Syahrul, Fahjri; Br Karo, Elza Azhari; Sinuhaji, Ezlina; Harefa, Erdiawan; Zega, Fajar; Gulo, Emong Ikhtiar Bernando (Pusat Pengembangan Olahraga Universitas Pahlawan, 2025)
Purpose of the study: This systematic review aimed to evaluate the effectiveness of various training methods for improving the performance of table tennis athletes and to provide evidence-based recommendations for coaches and practitioners across different competitive levels. Materials and methods: A comprehensive systematic search was conducted across six major databases (Web of Science, PubMed, Scopus, SPORTDiscus, Google Scholar, and ScienceDirect) from inception to September 2025. Studies were included if they examined training interventions in table tennis players and reported quantitative performance outcomes. The PRISMA 2020 guidelines were strictly followed for reporting. Quality assessment was performed using the Cochrane Risk of Bias tool (RoB 2.0) for randomized controlled trials and ROBINS-I for non-randomized studies. Meta-analysis was conducted using random-effects models with standardized mean differences and 95% confidence intervals. Results: Fifty-four studies met the inclusion criteria, involving 2,959 participants (mean age: 16.8 ± 4.2 years). High-intensity interval training (HIIT) demonstrated the highest effectiveness (Effect Size = 0.89, 95% CI: 0.75-1.03), followed by plyometric training (ES = 0.82, 95% CI: 0.68-0.96) and multiball training (ES = 0.78, 95% CI: 0.61-0.95). Physical training and core training showed moderate effectiveness (ES = 0.65-0.71), while technical training demonstrated the smallest effect size (ES = 0.58, 95% CI: 0.44-0.72). Fifty-two percent of studies showed low risk of bias, with consistent positive effects across different age groups and skill levels. Conclusions: HIIT, plyometric, and multiball training methods are most effective for improving table tennis performance compared to traditional training approaches. These sport-specific, high-intensity methods align with the physiological demands of table tennis and provide superior performance enhancements. The findings provide robust evidence-based guidance for developing optimal training programs for table tennis athletes across recreational to competitive levels.